High-Resolution Synchrotron μXRD and μXRF for Local Phase and Elemental Analysis in Suspension Plasma Sprayed Environmental Barrier Coatings - Nayak, Chinmayee; Hasani, Arman; Vinay, Gidla; Mäkila, Ermei; Owusu, Ebenezer; Kamboj, Nikhil; Makowska, Malgorzata Grazyna; Lynam, Alex; Romero, Acacio Rincon; Goel, Sneha; Hussain, Tanvir; Salminen, Antti; et al. (Springer Nature, 2026)
Suspension plasma spraying (SPS) enables the fabrication of environmental barrier coatings (EBCs) with complex multilayer architectures; however, degradation in such systems often initiates locally at buried interfaces, making it difficult to resolve using conventional laboratory-scale characterization techniques. In this work, the applicability of synchrotron-based micro-x-ray diffraction (µXRD), combined with micro-x-ray fluorescence (µXRF), is evaluated for the characterization of SPS-deposited ytterbium disilicate (YbDS) EBCs. An as-sprayed YbDS coating was investigated as a baseline case to examine differences between conventional XRD and spatially resolved µXRD, while an annealed and CMAS-exposed YbDS coating was studied as a service-relevant case to probe localized phase evolution. The samples were selected from previously optimized SPS process conditions and are not intended for direct comparison. Laboratory-scale XRD provided global phase information, whereas µXRD enabled layer-specific phase identification and resolved localized interfacial features. In the as-sprayed condition, µXRD confirmed phase-pure YbDS, resolved the crystallinity of individual coating layers, and verified the absence of unintended interfacial reaction phases that are not accessible by conventional XRD. In the annealed + CMAS-exposed coating, µXRD and µXRF revealed the formation of a calcium–ytterbium–silicate oxyapatite phase confined to the YbDS/Si interface, highlighting the localized nature of CMAS-induced degradation. These results demonstrate that synchrotron microanalysis provides valuable complementary insight for probing localized phase evolution in thermally sprayed EBC systems.